Impact of germination on structural, functional properties and in vitro protein digestibility of sesame (Sesamum indicum L.) protein. (15th January 2022) - Di, Yan; Li, Xiang; Chang, Xiaowen; Gu, Ruijuan; Duan, Xiang; Liu, Fuguo; Liu, Xuebo; Wang, Yutang
Abstract: To enhance the functional properties and utilization of sesame protein, the impact of different germination treatments (0 d, 2 d, and 4 d) on the structural and functional properties of sesame protein was investigated in this study. The results showed that germination significantly increased the content of free sulfhydryl groups and the surface hydrophobicity of sesame protein, indicating that the protein molecular structure was unfolded. The high molecular weight protein bands gradually disappeared, and the secondary structure of the sesame protein was changed after germination. Moreover, germination led to changes in the foaming and emulsifying properties of sesame protein. The in vitro protein digestibility and solubility of sesame protein were also increased after germination. These results suggested that germination treatment can improve the structural and functional properties of sesame protein and can be used as an effective approach to enhance the nutritional properties and processing value of plant seed protein. Graphical abstract: Image 1 Highlights: Germination increased the content of free sulfhydryl groups of sesame protein. Germination significantly increased the surface hydrophobicity of sesame protein. The high molecular weight proteins were hydrolyzed after germination. Germination improved the functional properties and IVPD of sesame protein. Germination changed the thermal properties of sesame protein.